Orientación Familiar Y Rendimiento Académico De Los Estudiantes De Bachillerato Del Colegio Fiscal “Enrique Ponce Luque” Del Cantón Quevedo, Provincia De Los Ríos.” - Falcones Suarez Gladys (2014)
In this thesis study we have determined the methodological strategies in order to improve teaching and student learning Education Unit Enrique Ponce Luque, by applying talks family counseling workshops to help improve the level of academic performance and student learning. Allowing them a family harmonious development that leads to better school performance favorably to help students of the institution to be more motivators. This field research helps us improve the quality of family life in order to guide students through the analytical deductive inductive method, and thoughtful.